The Influence of Mithraism on Christianity - Akhondi, Zohreh; Akbari, Amir (Journal of History Culture and Art Research, 2017)
Abstract In religious studies, the influence of mythology and religion on each other is worthy of deliberation. Among the religions, Mithraism, the ancient Persian pre-Zoroastrian religion, and Christianity have the most similar and common points that indicate logical influence. Religions influence each other and sometimes over laps, of course. As regards, Mithraism had priority over Christianity; however, there is no way for religious scholars to consider Christianity as the substitution of Mithraism. This study intends to present influence of Mithraism on Christianity by following traces and evidences in history.